Increasing Human Resource Capacity Through Workshop 7 (Seven) Habits in Elementary and Middle Education Council PNF PCM Gresik - Sukaris, Sukaris; Indro Kirono; Heru Baskoro; Nadhirotul Laily; Alkusani (OJS Universitas Muhammadiyah Gresik, 2025)
Increasing the capacity of human resources (HR) in elementary schools is urgent, especially amidst the challenges of low initiative, weak institutional vision, and minimal character training for teachers and education personnel. This community service activity aims to strengthen HR competency and work culture at SD Muhammadiyah 3 Gresik through training based on The 7 habits of highly effective people. The methods used include three main stages: initial discussion with partners through Focus Group Discussion (FGD) to map problems; participatory and reflective training that integrates seven effective habits into educators' work routines; and evaluation based on questionnaires and personal reflection. The training was delivered contextually and interactively through case studies, simulations, and group discussions. The results of the activity showed positive changes in the way of thinking, time management, and collaboration patterns between participants. Teachers became more proactive, had long-term planning, and were better able to work in teams synergistically. The evaluation also showed increased motivation and awareness of the importance of balance between professional duties and self-development. This activity concluded that the 7 Habits training was effective in building productive and collaborative work characters in elementary education environments. It is recommended that this training be conducted periodically and accompanied by follow-up mentoring to ensure the sustainability of the impact and the formation of an adaptive work culture.